Konstruksi Makna Bekerja Sukarelawan Kesehatan Mental sebagai Praktisi Public Relations Officer pada Yayasan Non Profit - Afradiva Mochammad Sidik; Mohammad Subur Drajat (Bandung Conference Series: Public Relations, 2022)
Abstract. According to data from the Ministry of Health of the Republic of Indonesia as of October 2021, 1 in 5 Indonesians has the potential to have mental problems and mental disorders. The Rangkoel Care Indonesia Foundation is here to help solve these problems. The Rangkoel Care Indonesia Foundation has a public relations officer. Based on a sense of caring for others and wanting to increase public mental health awareness is the background why someone wants to work as a public relations officer at the Rangkoel Care Indonesia Foundation. The motives, experiences and meanings of someone wanting to work as a public relations officer at the non-profit Rangkoel Care Indonesia Foundation are the research questions that will be investigated. This study uses a qualitative paradigm with phenomenological methods. Researchers try to be able to unravel the various phenomena that exist. In-depth interviews, observation and documentation were chosen as data collection techniques. In-depth interviews were conducted with informants, public relations officers and the chairman of the Rangkoel Care Indonesia Foundation. Data reduction, presentation and verification were chosen as research data analysis techniques. Data triangulation was chosen as a way to test the validity of the data through sources, methods, investigators and theories. It was studied using George Herbert's theory of symbolic interaction, Peter L Berger's theory of social reality construction together with Alfred Schutz's phenomenological approach in the hope of disentangling evidence, data and information on phenomena brighter than light. There are research results in the form of a motive for seeking work connections, interest in the world of mental health, maximizing self-potential, utilization of scientific disciplines, a sense of humanity and spiritual values. In addition, there are work experience values ​​such as innovative, consistent, hardworking, compassionate, integrity, leadership and a long and deep mind. Thus, the meaning of working to help, humanity and spirituality is formed in life. Abstrak. Menurut data dari Kementerian Kesehatan Republik Indonesia per Oktober tahun 2021, bahwa 1 dari 5 orang Indonesia berpontesi meimiliki masalah mental dan gangguan kejiwaan. Yayasan Rangkoel Care Indonesia hadir guna membantu menyelesaikan permasalahan tersebut. Yayasan Rangkoel Care Indonesia mempunyai public relatons officer. Dengan dasar rasa kepedulian terhadap sesama dan ingin meningkatkan kesadaran kesehatan mental masyarakat merupakan latar belakang mengapa seseorang ingin bekerja sebagai public relations officer di Yayasan Rangkoel Care Indonesia. Motif, pengalaman dan makna seseorang mau bekerja sebagai public relations officer di Yayasan non profit Rangkoel Care Indonesia menjadi pertanyaan-pertanyaan penelitian yang akan diteliti. Penelitian ini menggunakan paradigma kualitatif dengan metode fenomenologi. Peneliti berusaha untuk bisa mengurai berbagai fenomenan yang ada. Wawancara mendalam, observasi dan dokumentasi dipilih sebagai teknik pengumpulan data. Wawancara mendalam dilakukan kepada informan public relations officer dan ketua dari Yayasan Rangkoel Care Indonesia. Reduksi, penyajian dan verifikasi data dipilih sebagai teknik analisi data penelitian. Tringulasi data dipilih sebagai cara uji keabsahan data melalui sumber, metode, penyidik dan teori. Dikaji menggunakan teori interaksi simbolik George Herbert, teori konstruksi realtitas sosial Peter L Berger bersama pendekatan fenomenologi Alfred Schutz dengan harapan dapat mengurai bukti, data dan informasi fenomena lebih terang daripada cahaya. Terdapat hasil penelitian berupa motif pencarian koneksi kerja, ketertarikan dunia kesehatan mental, pemaksimalan potensi diri, pemanfaatan disiplin ilmu, rasa kemanusiaan dan nilai-nilai spiritual. Selain itu, terdapat nilai pengalaman kerja seperti inovatif, konsisten, pekerja keras, penyayang, integritas, jiwa kepemimpinan dan pikiran yang panjang serta mendalam. Sehingga, terbentuk makna bekerja tolong menolong, kemanusiaan dan spiritual dalam hidup.